Tax rates and tax evasion: an empirical analysis of the structural aspects and long-run characteristics in Italy - Bruno Chiarini; Elisabetta Marzano; Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2008)
By using official time series of the Italian evaded VAT base (Ministry of Finance) for the period 1980-2004 we investigate empirically the long-run characteristics of tax evasion and the relationship with the tax burden. We focus on three important issues not analyzed so far. First, using different measures of aggregate economic activity as reference variables in estimating the average tax burden, we investigate the size and dynamics of the over-burden traceable back to tax evasion. Second, exploiting cointegration techniques, we quantify the elasticity between tax evasion and the average tax rate in Italy. We then comment on the complex dynamic interaction between tax burden and tax evasion, to ascertain whether in the Italian experience there is evidence for any vicious circle between them.
urn:nbn:de:101:1-2008042116
Keywords: H30; 330; Tax evasion; VAT evasion; effective tax rate; apparent tax rate; VECM; Steuerflucht; Steuerkriminalität; Steuerbelastung; Umsatzsteuer; Steuertarif; Italien